2022
DOI: 10.1002/dev.22331
|View full text |Cite
|
Sign up to set email alerts
|

Processing of task‐irrelevant sounds during typical everyday activities in children

Abstract: Our ability to focus on a task and ignore task‐irrelevant stimuli is critical for efficient cognitive functioning. Attention control is especially required in the auditory modality as sound has privileged access to perception and consciousness. Despite this important function, little is known about auditory attention during typical everyday activities in childhood. We investigated the impact of task‐irrelevant sounds on attention during three everyday activities ‐ playing a game, reading a book, watching a mov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…The P2 component typically peaks at the centro-parietal regions of the brain (Dong et al, 2010;van Hooff et al, 2011). In previous studies, the P2 component has been found to be significantly reduced in congruent stimuli (Freunberger et al, 2007;Gruber & Müller, 2005), including sound stimuli (Zioga et al, 2020;Debnath & Wetzel, 2022). The P2 component was also found to be lower in response to high-order online shopping webpages compared to low-order online shopping webpages (Shang et al, 2020).…”
Section: Natural Sounds and Early Attentional Congruencymentioning
confidence: 91%
“…The P2 component typically peaks at the centro-parietal regions of the brain (Dong et al, 2010;van Hooff et al, 2011). In previous studies, the P2 component has been found to be significantly reduced in congruent stimuli (Freunberger et al, 2007;Gruber & Müller, 2005), including sound stimuli (Zioga et al, 2020;Debnath & Wetzel, 2022). The P2 component was also found to be lower in response to high-order online shopping webpages compared to low-order online shopping webpages (Shang et al, 2020).…”
Section: Natural Sounds and Early Attentional Congruencymentioning
confidence: 91%